Meteorological influences on airborne pollen and spores in Johannesburg (Gauteng), South Africa - Linus B. Ajikah; Sarah J. Roffe; Frank H. Neumann; Marion K. Bamford; Nanike Esterhuizen; Dilys Berman; Jonny Peter (Aerobiologia, 2023)
Airborne fungal spores and pollen (aerospora), synergistic with air pollution, are key triggers of allergic respiratory diseases. Effective diagnosis and treatment requires up-to-date location-specific knowledge on the temporal variability of aerospora types and levels. Johannesburg is the largest city in South Africa and has grown substantially in three decades, with changes in ground cover, population density and air pollution, yet until now, no continuous aerospora sampling has occurred. We present a daily two-year (August 2019–July 2021) aerospora assemblage for Johannesburg and explore temporal characteristics of 13 dominant aerospora in relation to daily meteorological variables (pressure, rainfall, relative humidity, temperature and wind characteristics). February–July, July–September and January-July represent high-risk periods for fungal spores [( Alternaria alternata (Fries. ex Keissler), Ascospores, Aspergillus niger (Van Tieghem) , Penicillium chrysogenum (Thom), Cladosporium graminum (Corda), Epicoccum nigrum (Link), Helminthosporium solani (Durieu and Montagne) Nigrospora sphaerica (Saccardo ex. Mason), Smuts Ustilago nuda ( Jensen ex. Rostrup) and Torula herbarum (Link)], trees ( Cupressus , Morus and Platanus ) and grass (Poaceae), respectively. Using a generalised additive model, results show that daily meteorological characteristics explained 7–32% of daily aerospora variability, with the largest effect on tree pollen. Rainfall, relative humidity and temperature influenced daily fungal spore and Poaceae counts, with moderate/low rainfall (